Classics in total synthesis - Nicolaou, K. C (VCH, 1996)
This book is a must for every synthetic chemist. Authors present the most remarkable and ingenious total syntheses from outstanding synthetic organic chemists. To make the complex strategies more accessible, especially to the novice, each total synthesis is analyzed retrosynthetically. The authors then carefully explain each synthetic step and give hints on alternative methods and potential pitfalls. Numerous references to useful reviews and the original literature make this book an indispensable source of further information. Special emphasis is placed on the skillful use of graphics and schemes: Retrosynthetic analyses, reaction sequences, and stereochemically crucial steps are presented in boxed sections within the text